A Novel Method for Preparation of Zn-Doped CuInS2 Solar Cells and Their Photovoltaic Performance - Cheng-Hsiung Peng; Chyi-Ching Hwang (The Scientific World Journal)
In this study, a novel method was proposed to synthesize high quality Zn-doped CuInS2 nanocrystals under high frequency magnetic field at ambient conditions. The magnetic Zn-doping gave superparamagnetic heating of the resulting nanocrystals via magnetic induction, causing an accelerating growth rate of the doped CuInS2 under ambient conditions faster than conventional autoclave synthesis. Shape evolution of the Zn-doped CuInS2 nanocrystals from initially spherical to pyramidal, to cubic, and finally to a bar geometry was detected as a function of time of exposure to magnetic induction. These colloidal solvents with different shaped nanocrystals were further used as “nanoink” to fabricate a simple thin film solar device; the best efficiency we obtained of these crystals was 1.01% with a 1.012 μm thickness absorber layer (bar geometry). The efficiency could be promoted to 1.44% after the absorber was thickened to 2.132 μm.